Development of Self-Dietary Assessment Application “Diary NutriMe” as a Nutrition Assistance Tool for Overweight and Obese Adolescents: Pengembangan Aplikasi Self-Dietary Asessment "Diary NutriMe" sebagai Media Pendampingan Gizi bagi Remaja Overweight dan Obesitas - Haryana, Nila Reswari; Azbi, Cinta Maulida; Sandy, Yatty Destani; Firmansyah, Hardi; Rosmiati, Risti (Amerta Nutrition, 2024)
Background: Inadequate nutritional intake is often influenced by lack of knowledge among adolescents regarding the quantity and types of food they should consume, impacting their nutritional status. With technology being an integral part of modern life, it can be leveraged to improve adolescents’ dietary practices by enhancing their knowledge of balanced nutrition. Objectives: To develop the self-dietary assessment application, Diary NutriMe, as a nutritional assistance tool for overweight adolescents to improve their nutritional knowledge and dietary intake. Methods: This study employed the Rapid Application Development (RAD) method. The feasibility assessment of the Diary NutriMe application was conducted by material and media experts using a checklist questionnaire with a Likert scale ranging from 1 (poor) to 5 (excellent), categorized into five levels: highly feasible to not feasible. The implementation involved improving nutritional knowledge among 36 overweight/obese adolescent students. Results: The application features included a login system, nutritional status calculation, nutrient requirement estimation, food intake records, physical activity logs, a collection of nutrition education materials, and a chat feature. The material feasibility assessment received an average score of 90.7%, categorized as highly feasible, while the media feasibility assessment received an average score of 86.7%, also categorized as highly feasible. Statistical analysis using a T-test indicated no significant difference in respondents’ knowledge (p-value=0.51). However, there was an increase in the average nutritional knowledge score by 7.7 points before and after using the Diary NutriMe application. Conclusions: The Diary NutriMe application is highly feasible as a nutritional assistance tool for adolescents with overweight conditions.